Remote Working and Employee Engagement: A Case in Kathmandu Valley - Karki, Ashma (Nepalese Journal of Economics, 2025)
This study examines the remote working and employee engagement: A case in Kathmandu Valley. Employee engagement is the dependent variable. The selected independent variables are flexible working arrangements, internet connection, electric supply, working schedule and training. The primary source of data is used to assess the opinion of respondents regarding flexible working arrangements, internet connection, electric supply, working schedule, training and employee engagement. The study is based on primary data of 143 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the remote working and employee engagement: A case in Kathmandu Valley. The study showed a positive impact of working schedule on employee engagement. It indicates that f lexible working schedule leads to better employee engagement. Similarly, the study showed a positive impact of training on employee engagement. It indicates that effective training motivates remote workers to enhance the employee engagement. Likewise, the study showed a positive impact of flexible working arrangements on employee engagement. It indicates that higher the flexible working arrangements, higher would be the employee engagement. Further, the study showed a positive impact of electric supply on employee engagement. It indicates that stable electric supply leads to increase in employee engagement. In addition, the study showed a positive impact of internet connection on employee engagement. It indicates that stable internet connection encourages remote workers to get engaged.